KL1333, a Novel NAD+ Modulator, Improves Energy Metabolism and Mitochondrial Dysfunction in MELAS Fibroblasts - Seo, Kang-Sik; Kim, Jin-Hwan; Min, Ki-Nam; Moon, Jeong-A; Roh, Tae-Chul; Lee, Mi-Jung; Lee, Kang-Woo; Min, Ji-Eun; Lee, Young-Mock (Frontiers in Neurology, 2018)
Mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS), one of the most common maternally inherited mitochondrial diseases, is caused by mitochondrial DNA mutations that lead to mitochondrial dysfunction. Several treatment options exist, including supplementation with CoQ10, vitamins, and nutrients, but no treatment with proven efficacy is currently available. In this study, we investigated the effects of a novel NAD+ modulator, KL1333, in human fibroblasts derived from a human patient with MELAS. KL1333 is an orally available, small organic molecule that reacts with NAD(P)H:quinone oxidoreductase 1 (NQO1) as a substrate, resulting in increases in intracellular NAD+ levels via NADH oxidation. To elucidate the mechanism of action of KL1333, we used C2C12 myoblasts, L6 myoblasts, and MELAS fibroblasts. Elevated NAD+ levels induced by KL1333 triggered the activation of SIRT1 and AMPK, and subsequently activated PGC-1α in these cells. In MELAS fibroblasts, KL1333 increased ATP levels and decreased lactate and ROS levels, which are often dysregulated in this disease. In addition, mitochondrial functional analyses revealed that KL1333 increased mitochondrial mass, membrane potential, and oxidative capacity. These results indicate that KL1333 improves mitochondrial biogenesis and function, and thus represents a promising therapeutic agent for the treatment of MELAS.